2014
DOI: 10.1080/03601234.2014.938559
|View full text |Cite
|
Sign up to set email alerts
|

17 β-estradiol and 17 α-ethinylestradiol mineralization in sewage sludge and biosolids

Abstract: Natural steroid estrogens (e.g., 17 β-estradiol, E2), synthetic steroid estrogens (e.g., 17 α-ethinylestradiol, EE2) and pharmaceutical antibiotics (e.g., ciprofloxacin) are chemicals detected in biosolids and sewage sludges because they partition into the solids fraction during the wastewater treatment process. This research utilized a three-way factorial design (six media × two estrogens × three antibiotic treatments) to quantify cumulative E2 and EE2 mineralization over 133 d (MAX) in a range of sewage slud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Biosolids and sewage sludge have been shown to be favorable media for the mineralization of natural and synthetic steroid estrogens. Rose et al (2014) demonstrated biosolids prove more favorable for the mineralization of natural steroid estrogens (17 β-estradiol) and sewage sludge, particularly pretreatment holding lagoons, than for synthetic estrogens (17 α-ethinylestradiol).…”
mentioning
confidence: 99%
“…Biosolids and sewage sludge have been shown to be favorable media for the mineralization of natural and synthetic steroid estrogens. Rose et al (2014) demonstrated biosolids prove more favorable for the mineralization of natural steroid estrogens (17 β-estradiol) and sewage sludge, particularly pretreatment holding lagoons, than for synthetic estrogens (17 α-ethinylestradiol).…”
mentioning
confidence: 99%